2012
DOI: 10.1542/peds.2011-3357
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Sensory Capacity of the Preterm Infant: Manual Perception of Shape From 28 Gestational Weeks

Abstract: Development/Behavioral Issues the following collection(s):This article, along with others on similar topics, appears in WHAT THIS STUDY ADDS: The preterm infant, even when very immature (from 28 gestational weeks), is endowed with tactile sensory abilities: the exploration and memorization of an object by touch, the discrimination of a novel object, and the recognition of a familiar object after interference. abstract OBJECTIVE: Recent studies have shown that from the postconceptional age of 33 weeks, preterm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 20 publications
2
16
0
2
Order By: Relevance
“…Recent studies on haptic touch evidenced that before their fifth day of life, full-term newborns can discriminate object textures (Molina & Jouen, 2003), weights (Hernandez-Reif, Field, Diego, & Largie, 2001), or shapes (Streri, Lhote, & Dutilleul, 2000). Premature newborns, at least at 28 weeks PC, can also discriminate different objects by their shape (Marcus, Lejeune, Berne-Audéoud, Gentaz, & Debillon, 2012).…”
Section: Current Knowledge Of Newborns' Umwelt Tactile Perceptionmentioning
confidence: 99%
“…Recent studies on haptic touch evidenced that before their fifth day of life, full-term newborns can discriminate object textures (Molina & Jouen, 2003), weights (Hernandez-Reif, Field, Diego, & Largie, 2001), or shapes (Streri, Lhote, & Dutilleul, 2000). Premature newborns, at least at 28 weeks PC, can also discriminate different objects by their shape (Marcus, Lejeune, Berne-Audéoud, Gentaz, & Debillon, 2012).…”
Section: Current Knowledge Of Newborns' Umwelt Tactile Perceptionmentioning
confidence: 99%
“…Infants begin to move and interact with their environment prior to birth, setting the stage for a lifetime of interaction between the sensory and motor systems. While early fetal movement appears to be spontaneously generated, both rat and human research suggests that movement in the prenatal period can be modified using sensory input . At birth, infants are exposed to a whole new world of sensory input and motor demands.…”
Section: Definitions Of Key Terminologymentioning
confidence: 99%
“…These infants failed to display any effective discrimination between the smooth and angular objects, unlike the infants in the silence group. Previous studies have shown that preterm infants do have the ability to memorise tactile information about the specific features of an object and to detect differences with another object . Our study revealed that the presence of a voice had a negative impact on their sensory learning.…”
Section: Discussionmentioning
confidence: 47%